Housing wealth and consumption in Malaysia: new evidence - Wong, Wang Li; Chin, Lee; Wong, Kelly Kai Seng; Tee, Chee Lip (Universiti Putra Malaysia Press, 2019)
This study discusses the impact of housing market on economy through consumption channel. The discussion includes comparing the past and current relationship of housing wealth and consumption as well as the challenges of government in making housing policies. In summary, housing wealth exhibit a negative relationship in the past (1999 – 2011) due to the wealth channel is stifle, consumer perceive house price increase as housing cost increase, thus reduce spending. However, the scenario had turned into an unexpected manner, where an asymmetric relationship found in the current state (2000 – 2017). This probably due to the financial innovation that began in year 2004 and afterward financial liberalization in year 2009.